One Gate Digital Archive for Elementary School Digitalisation - Kania Puspa Dewi; Christina Ismaniati; Rahayu Condro Murti (Journal of Innovation in Educational and Cultural Research, 2023)
Archive management is an aspect that must be managed by schools, which still receive a lack of attention despite its importance. This lack of attention to management can be seen in elementary schools, which only rely on one school operator to manage the archives because of a lack of employees. As a result, a lot of data is not archived, damaged, lost, and unorganized. This study aims to produce a web-based one-gate digital archive by utilizing the learning.id account feature that is owned by educators and educational staff in Indonesia. The creation of a one-gate digital archive is carried out to improve the school’s archive management and to increase school digitalization, so that educational services increase. This research uses plomp’s model development research. The advantage of using a one-gate digital archive is that it allows schools to easily change the web's appearance and features needed with low-cost. The result showed that the developed one-gate digital archive was valid and reliable, with an average score of 4,7, which was included in the excellent category. The existence of one gate digital archive is expected to help the principal and teachers in managing the archive. This research still needs to examine the effectiveness of this one-gate digital archive, so further research needs to be done.